Who Intends to Enter the Formal Sector the Most? Individual-Level Determinants of Formal Job Selection in Indonesia - Susilo, Susilo; Pratomo, Devanto Shasta; Setyanti, Acellina Muara; Wicesa, Nayaka Artha; Prestianawati, Silvi Asna; Rasli, Amran; Abas, Imelda Hermilinda (International Journal of Social Science and Business, 2024)
The informal sector in the labor market is often regarded as filled with low-quality, low-productivity, low-wage jobs. However, in Indonesia, the informal sector is important in absorbing more than half of the total workforce and providing subsistence wages for those not absorbed in the formal labor market. This study used SUSENAS microdata to determine the workforce determinants in working in the formal and informal sectors. The study results show that higher education, male gender, and living in an urban area increased one's chances of working in the formal sector. This study also found an inverted u-shaped curve on age, where a person's tendency to work in the formal sector would increase at the beginning of their productive age and decrease after entering the age of 27. Marital status in this study increased opportunities to work in the informal sector. This research may use to improve the labor policy and improve the job opportunity in both formal and informal sector.